ANALISIS KONSEP INSAN KAMIL DI ERA MODERN: IMPLEMENTASI DAN TANTANGAN PADA MADRASAH IBTIDAIYAH - Erlindah Dwi Rahayu; Nafi’ah Nashihah; Siti Mutmainah; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
This study examines the concept of insan kamil in Madrasah Ibtidaiyah (MI) as an orientation of Islamic education goals in the modern era. The rapid development of technology, globalization, and moral shifts among children require Islamic educational institutions to strengthen holistic educational values. The concept of insan kamil emphasizes the balance between spiritual, intellectual, emotional, and social dimensions in shaping the ideal Muslim personality. This research uses a qualitative approach through library research by analyzing classical and contemporary Islamic education literature. The results show that the implementation of the insan kamil concept in MI can be realized through integrative curriculum development, character education, habituation of worship, teacher exemplary behavior, and digital literacy based on Islamic values. In the modern era, MI not only functions as a place for knowledge transfer but also as a center for forming students with noble character, critical thinking, creativity, and strong religious commitment. Therefore, the concept of insan kamil remains highly relevant as the philosophical foundation of Islamic education to answer contemporary educational challenges.